A2.24 Activation of the NLRP3 inflammasome by an endogenous TLR2 ligand in rheumatoid arthritis. (13th February 2015) - Connolly, M; McGarry, T; Biniecka, M; Veale, DJ; Fearon, U
Abstract : Background/Objectives: The inflammasome is a large multiprotein complex which plays a key role in innate immunity by mediating the production of pro-inflammatory cytokines interleukin-1β (IL-1β) and IL-18. The most characterised inflammasome is NLRP3, activation of which results in numerous biological effects associated with infection, inflammation and autoimmune processes. While the inflammasome has traditionally been thought to regulate infection and inflammation, impaired mitochondrial metabolism may mediate this process. In this study we examined the interplay between the inflammasome and mitochondrial function following TLR2 activation. Methods: Mitochondrial mutagenesis was assessed by Random Mutation Capture Assay. Reactive oxygen species were measured by cellular detection assay. Primary RASFC and whole ex vivo synovial tissue were stimulated with a TLR2 agonist, PAM3CYSK4, in the presence of absence of N-Acetyl Cysteine (NAC). IL-1β and IL-18 expression was examined by PCR. NLRP3 expression was assessed by real-time PCR and western blot. To establish whether A-SAA activates TLR, human embryonic kidney (HEK) -TLR2 or -TLR4 cells were cultured in the presence of A-SAA and NFκB luciferase activity was examined. In parallel, the effect of A-SAA on RASFC function was examined in the presence of a specific neutralising anti-TLR2 mAb (1 μg/ml) and matched IgG isotype control Ab (1 μg/ml). RASFC proliferation, adhesion, chemokine expression and migration were assessed by proliferation assays, flow cytometry, Taqman PCR, ELISA and wound repair assays. Results: PAM3CYSK4 significantly induced mitochondrial mutagenesis and reactive oxygen species in RA synovial explants cultures and fibroblasts (p < 0.05). TLR2 activation increased transcript levels of inflammasome and pro-inflammatory mediators including IL-1, IL-18 and NLRP3. Furthermore, activation of TLR2 induced IL-6, IL-8, IL-1, IL-18 at a protein level, effects which were significantly inhibited in presence of NAC, an ROS inhibitor (all p < 0.05). Additionally, we demonstrated that A-SAA is an endogenous TLR2 ligand since it induced TLR2 mediated NF-κB lucifearse activity (p < 0.05), with no effect observed for NFκB in HEK-TLR4 cells. A-SAA significantly induced NLRP3 mRNA and protein expression. In parallel, A-SAA induced RASFC proliferation, ICAM-1 expression and migration, all of which were significantly inhibited in the presence of anti-TLR2 (all p < 0.05), further confirming its role as an endogenous TLR2 ligand. Conclusion: TLR2 induces mitochondrial dysfunction which plays a key role in the regulation of downstream inflammasome activation. TLR2-induced pro-inflammatory effects in RA may be mediated by endogenous secretion of A-SAA from the synovium at the site of inflammation.